DESKRIPSI TEORITIS, KERANGKA BERPIKIR DAN HIPOTESIS PENELITIAN - Abdul Kahar (Potret Pemikiran, 2015)
This study discusses theoretical descriptions, frameworks and research hypotheses. Communicative learning techniques are ways of delivering messages or information to targets that can be delivered through various methods that are assisted by several media in the form of images, Ohv, television and other media in accordance with the message conveyed and goals what you want to achieve. In this study two types of communicative learning will be discussed, namely simulation and recitation. Simulation is a form of play performed by participants to solve one form of problem, in accordance with established rules, and practice carrying out tasks that will be faced in everyday life. Recitation (recitation) can be equated with the method of giving assignments, the method of assigning assignments is one way of teaching that is characterized or characterized by the existence of problems or problems that are given by the teacher to be completed or mastered within the period agreed upon between teachers and students.Keywords: Theoretical Description, Simulation, Recitation Studi ini membahas tentang deskripsi teoritis, kerangka berpikir dan hipotesis penelitian.Teknik pembelajaran komunikatif adalah cara penyampaian pesan atau informasi kepada sasaran yang dapat disampaikan melaluiberbagai metode yang dibantu oleh beberapa media berupa gambar, Ohv, televisi dan media lainnya sesuai dengan pesan yang disampaikan dan tujuan yang ingin dicapai. Dalam penelitian ini akan dibahas dua macam pembelajaran komunikatif yaitu simulasi dan resitasi. Simulasi merupakan bentuk permainan yang dilakukan peserta untuk memecahkan salah satu bentuk permasalahan, sesuai dengan aturan yang telah ditetapkan, dan berlatih melaksanakan tugas-tugas yang akan dihadapi dalam kehidupan sehari-hari. Resitasi (recitation) dapat disamakan  dengan metode  pemberian tugas, metode pemberian tugas adalah salah satu cara mengajar  yang dicirikan atau ditandai oleh adanya  persoalan atau problematika yang  diberikan oleh guru untuk diselesailcan  atau dikuasai dalam  jangka waktu yang telah disepakati bersama  antaru guru dan siswa.Kata Kunci: Deskripsi Teoritis, Simulasi, Resitasi